1970
DOI: 10.1192/bjp.116.532.255
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Psychiatric Consequences of Huntington's Disease

Abstract: The complex interaction of genetic and environmental influences in Huntington's disease results in successive generations living in deteriorating social circumstances. As the disease is untreatable (other than by palliative measures), spouses and unaffected children also suffer indirectly from its socio-psychiatric consequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
78
1
1

Year Published

1972
1972
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(85 citation statements)
references
References 3 publications
5
78
1
1
Order By: Relevance
“…There was no evidence of cognitive decline coinciding with the initial psy-chiatric presentation in either of our two cases. Mood symptoms and disorders in HD have been well described in the literature (4,18). One study found that in a HD population, up to 32.5% met DSM III-R criteria for major affective disorders and 9% for dysthymia (4).…”
Section: Discussionmentioning
confidence: 99%
“…There was no evidence of cognitive decline coinciding with the initial psy-chiatric presentation in either of our two cases. Mood symptoms and disorders in HD have been well described in the literature (4,18). One study found that in a HD population, up to 32.5% met DSM III-R criteria for major affective disorders and 9% for dysthymia (4).…”
Section: Discussionmentioning
confidence: 99%
“…Although an early study described anxiety as the most common prodromal symptom, occurring in 12% of 102 patients (Dewhurst 1970), it is the symptoms of anxiety that are more often seen rather than a primary anxiety disorder. This group of symptoms is likely to be secondary to underlying cognitive changes and should be considered as a separate neuropsychiatric behaviour disorder.…”
Section: Anxiety Disordersmentioning
confidence: 99%
“…[7] Three main theories exist as to why some HD patients present with psychosis while others do not: (i) genetically, these patients have a different subtype of HD, [7] possibly linked to the length of the CAG repeats; [9,10] (ii) cooccurrence in a 'vulnerable' brain [7] and (iii) developmental effect due to the stress of growing up in a disrupted family structure secondary to the presence of serious illness, of which one has a 50% chance of developing. [11][12][13] Currently, although we are unable to distinguish clinically between the psychosis of HD and schizophrenia, there are various possible pointers. A recent review on secondary psychosis suggests that several questions can be asked to determine whether the psychosis is as a result of a general medical condition (GMC).…”
Section: Diagnostic V Predictive Testingmentioning
confidence: 99%